A study to compare the efficacy, inadequacy and patient knowledge of pipelle and dilatation and curettage (D&C) for patients with abnormal uterine bleeding - Meeta Gupta; Poonam Yadav; Narita Jamwal; Vanita Gupta (Barpeta Obstetrics and Gynaecological Society, 2021)
Objective: We aimed to assess the patient knowledge/choice for subsequent procedure, sampling adequacy, and diagnostic accuracy of Pipelle endometrial sampling and conventional D&C in patients with abnormal uterine bleeding (AUB). Methods: This study included total 443 women >40 years of age, with AUB requiring endometrial evaluation. Pipelle biopsy was done without cervical dilation followed by D&C. The histopathology of both the procedures was compared, considering histopathology of the D&C sample as gold standard. Outcomes were compared among the two procedures. Results: Overall accuracy of the Pipelle device was 399(90.67%). Pipelle device was inadequate in 29(6.55%) cases. Pipelle was 100% sensitive and 100% specific for diagnosis of atrophy, endometritis and endometrial carcinoma each. Pipelle was 100% sensitive for diagnosis of proliferative endometrium and secretory endometrium each and 96.48% and 97.92% specific respectively with excellent AUC of 0.98 and 0.99 respectively. Patients' knowledge/choice for subsequent procedure and procedure associated pain was significantly less for the Pipelle biopsy as compared to D and C. Conclusion: Pipelle is a good, relatively painless, cheap OPD procedure for endometrial aspiration but with the disadvantage of sample inadequacy due to which its routine use remains an enigma for the patient and the doctor.